(3eTcGI GdeUGHjMs - (3hdj GdOjf eMeO Hf YHO Gddg GdJHQjRj,J (B737 (3g` s ((3YKeGf Hf Ydi GdTQhGfi s)
(3ChdgG (B:s
(3GdMeO ddg fMeOg hfSJYjfg hfSJZaQg CeG HYO aEf GdJeSc HgOjg dGjSJKHJ EdG HGdEaJbGA deG UOQ ef eTcGJg hcGf cJG GdeUGHjM GdPi Ufag GdEeGe GdHZhi CLeY cJGH Ufa ai HGHg s
(3BNQgG (B:s
(3CfJe JJehf SHYjf CeI CfJe NjQgG hCcQegG Ydi Gddg QhGg GdJQePi hGHf eGLg hGdOQGei , hbGd GdJQePi (B: (3gPG MOjK (B[ (3MSf (B] s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG JbjjOGJ hHBNQgG SeGYGJs
(3ai ChdgG JedcGJ CbOegG SfI (B1160(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdMOjK h GdeUWdMs